Organizational and psychological features of successful democratic enterprises: A systematic review of qualitative research - Unterrainer, Christine; Weber, Wolfgang G.; Höge, Thomas; Hornung, Severin (Frontiers in Psychology, 2022)
In organizational psychology the positive effects of democratically structured enterprises on their employees are well documented. However, the longstanding viability as well as economic success of democratic enterprises in a capitalistic market environment has long been contested, for instance, giving rise to widespread endorsement of the “degeneration thesis” and the so-called “iron law of oligarchy”. By investigating 70 qualitative studies that examined altogether 67 democratic enterprises, plus the Mondragon Cooperative Cooperation network, within the last 50 years, the present systematic review provides evidence that such enterprises are also able to economically survive and prosper. The majority of studied enterprises (61.1%) either resisted pressures towards democratic degeneration or subsequently regenerated after undergoing degenerative processes. Only 10.4% fully degenerated in accordance with the degeneration thesis and the “iron law of oligarchy”, while 28.4% of the democratic enterprises showed diverse and mixed forms of degeneration and regeneration tendencies, indicating that the notion of an “iron law” needs to be rejected and revised. Further, this systematic review provides an overview of organizational and external conditions, non-/democratic or non-/participative practices and psychological phenomena that contribute to the degeneration, regeneration and resistance to degeneration (i.e., retention). The described examples of such practices and phenomena may help practitioners to implement and maintain democratic structures and processes in contemporary organizations.